Defensive and adverse energy‐related molecular responses precede tris (1, 3‐dichloro‐2‐propyl) phosphate cytotoxicity. Issue 5 (15th July 2015) - Zhang, Jinkang; Williams, Timothy D.; Chipman, James K.; Viant, Mark R.
Abstract: To understand the potentially adverse effects of human exposure to tris (1, 3‐dichloro‐2‐propyl) phosphate (TDCIPP) and explore the underlying molecular mechanisms, combined transcriptomic and metabolomic approaches were employed to investigate the molecular responses of two human cell lines exposed to different concentrations of TDCIPP. Comparative analyses of transcriptional and metabolic profiles of HepG2/C3A and A549 cells were performed after exposure to 1, 10 and 100 μM TDCIPP for 24 and 72 h. Stress responses (e.g. xenobiotic metabolism and ABC transporter pathways) were observed at the transcriptional level after 24‐h exposure to a sub‐cytotoxic concentration (10 μM). Transcription of an energy metabolism‐related pathway (oxidative phosphorylation) was down‐regulated more severely at 100 μM TDCIPP exposure, accompanied by the suppression of pathways relevant to cell proliferation (e.g. cell cycle and DNA replication), while no significant cytotoxic effects were observed. Functional metabolic changes were observed after 72 h in HepG2/C3A cells exposed to 100 μM TDCIPP that corresponded to changes detected at the transcriptional level after 24 h. Taken together, defensive responses to chemical exposure and energy‐related changes both precede the cytotoxic effects of TDCIPP in HepG2/C3A cells. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : To investigate the potential adverse effects of human exposure to tris (1, 3‐dichloro‐2‐propyl) phosphate (TDCIPP), the cytotoxicity of this flame retardant to HepG2/C3A and A549 cells was evaluated by CCK‐8 assays. The molecular responses to TDCIPP exposure were investigated using transcriptomic and metabolomic approaches. Defensive responses (e.g. xenobiotic metabolism) as well as energy‐related changes were observed, which preceded the cytotoxic effects of TDCIPP in HepG2/C3A cells.